Implications of climate change on surface temperature in North Indian states: evidence from CMIP6 model ensembles - Awasthi, Amit; Pattnayak, Kanhu Charan; Tandon, Aayushi; Sarkar, Abhijit; Chakraborty, Monojit (Frontiers in Environmental Science, 2023)
This paper presents a comprehensive case study using CMIP6 models to investigate temperature behaviour in the states of North India under 1.5°C and 2°C warming scenarios.Comparisons are made between observed surface temperature data from the Climatic Research Unit (CRU) and ensemble mean simulations from CMIP6. Results indicate that CMIP6 ensemble mean simulations effectively depict observed climatological patterns of surface temperature with negligible discrepancies. Under both the 1.5°C and 2°C warming scenarios, extreme temperatures show an increase compared to the preindustrial and present periods, suggesting an elevated risk of future severe heat events. Temperature changes relative to the preindustrial period are around 1.5°C, 3°C, and 4.5°C for the present, 1.5°C, and 2°C scenarios, respectively. Return period analysis shows a significant temperature rise of approximately 4.5 degrees over a return time of 60 years. These findings highlight the importance of climate models, valuable for impact studies, and emphasize the need to accurately enhance future model iterations' precision in simulating regional climates. Urgent climate change mitigation strategies are vital to curb temperature rise and mitigate potential adverse impacts on the region.In conclusion, this study provides critical insights into North India's climate behavior, underscoring the significance of proactive measures to effectively address climate change challenges within the region.